2022
DOI: 10.1186/s43163-022-00281-3
|View full text |Cite
|
Sign up to set email alerts
|

An extremely rare presentation of non-Hodgkin lymphoma in the head and neck: a case report

Abstract: Background Non-Hodgkin lymphoma (NHL) frequently presents as extra-nodal involvement, although primary diffuse large B cell lymphoma of extra-nodal origin is a distinct entity. Different subtypes may have propensity for specific anatomic locations. In the head and neck region, diffuse large B cell lymphoma (DLBCL) is most commonly presented in the paranasal sinuses, jaws, and Waldeyer’s ring. DLBCL involving fibroadipose tissue and presenting as an extra-nodal mass is extremely unusual, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The patient's history of multiple benign cysts of various sizes could have made the diagnosis easy to miss, assuming a presumptive diagnosis of a benign cyst. The presentation described today is not often seen [2][3] and is considered a high-grade lymphoma [4][5]. Of all forms of DLBCL, extranodal forms only comprise 34.48% [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The patient's history of multiple benign cysts of various sizes could have made the diagnosis easy to miss, assuming a presumptive diagnosis of a benign cyst. The presentation described today is not often seen [2][3] and is considered a high-grade lymphoma [4][5]. Of all forms of DLBCL, extranodal forms only comprise 34.48% [10].…”
Section: Discussionmentioning
confidence: 99%
“…Rare sites of extranodal DLBCL have been documented in the literature, including presentations in the scalp, testicles, bone, bladder, and nasal septum [2][3][6][7][8][9]. A recent 2022 study found that the percentages of extranodal DLBCL from years 2000-2015 at the age of 18 or greater in their search were as follows: GI tract 28.31%, nervous system 13.78%, head and neck 11.79%, skin and soft tissue 9.54%, genitourinary 7.24%, musculoskeletal 5.80%, respiratory tract 5.17%, pancreas and hepatobiliary 4.16%, endocrine organs 3.66%, heart and mediastinum 3.28%, breast 2.49%, bone marrow 2.47%, and others 2.30% [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations